Hematological reference intervals for Danish crossbred Landrace Yorkshire Duroc (LYD) pigs used in biomedical research - Kirstine Færgemand Præstegaard; Anne Winther-Larsen; Birgitte Saima Kousholt (Acta Veterinaria Scandinavica, 2025)
Abstract Background The health and welfare of pigs used in biomedical research is essential to research quality and compliance with the 3Rs (replacement, reduction, and refinement). Hematological variables are objective markers to quantitatively determine health issues and evaluate physiological differences before and after experimental procedures. There are no recent validated hematologic reference intervals (RIs) published for Danish crossbred Landrace Yorkshire Duroc (LYD) pigs to aid researchers and veterinarians in their decision-making. The objective of this study was to establish hematologic RIs for LYD pigs used for biomedical research. Blood samples were collected from healthy female LYD pigs (35–65 kg) and analyzed using the in-house ProCyte Dx Hematology Analyzer. Means with 90% confidence intervals for lower and upper limits were calculated according to guidelines by the American Society of Veterinary Clinical Pathology. Results Inspection of 141 pigs led to 133 blood samples available for analyses after exclusions due to clinical signs of disease, inadequate tube filling or presence of macroscopic clots. Thirty-two samples reported platelet abnormalities and upon further investigation these samples were excluded when calculating RIs for platelets and platelet indices. Other measurements were not affected. The RI for red blood cells, hemoglobin, hematocrit and white blood cells were 5.10–7.00 × 106/µL, 9.36–12.29 g/dL, 30.46–40.47%, and 11.73–25.00 × 103/µL, respectively. Conclusions Our study provides RIs for hematological variables in LYD pigs, revealing significant differences from published RIs of other breeds. These findings highlight the influence of factors like age, breed and health status on measurements, emphasizing the importance of using breed-specific RIs. This research supports the 3Rs, guiding better animal care and enhancing overall research quality.